KINETICS OF A SILICATE COMPOSITION GELATION IN PRESENCE OF REACTION RATE REGULATING COMPOUNDS - Titova, Olga; Trachevskyi, Vyacheslav; Grushak, Zoya; Stolyarova, Natalia (Proceedings of National Aviation University (archive), 2014)
The influence of organic and inorganic additions on the formation rate of the silicate gels standard systems – sodium silicate solution in model fresh water was studied. As a result of the experiments were selected optimum concentrations of additives - gelation time regulators